PROTEIN DIGESTION IN PERANAKAN ETAWA GOAT DUE TO DIFFERENT LEVELS OF DIETARY PROTEIN - Roosena Yusuf (Bioma : Jurnal Ilmiah Biologi, 2014)
The?é?á effort?é?á to?é?á increases?é?á milk?é?á production?é?á especially?é?á milk?é?á goat production?é?á can?é?á do?é?á with?é?á increasing?é?á quality?é?á of?é?á dietary?é?á and maintenance?é?á of?é?á goats,?é?á one?é?á of?é?á them?é?á was?é?á increasing?é?á level?é?á of dietary?é?á protein?é?á to?é?á increase?é?á protein?é?á metabolism?é?á in?é?á goats.?é?á The research purpose was to find out the acurate of?é?á dietary protein level to maximalize protein digestion?é?á in Peranakan Etawa goat. The?é?á materials?é?á used?é?á in?é?á the?é?á research?é?á were?é?á 12?é?á Peranakan?é?á Etawa goats at fourth month pregnancy and range of body weight 35,20 ?é???é?á 1,21?é?á kg?é?á (cv?é?á =?é?á 3,44%)?é?á with?é?á ?é???é?á 13?é?á month?é?á ages.?é?á The?é?á research design?é?á that?é?á used?é?á is?é?á completely?é?á randomized?é?á design?é?á one?é?á factor with three treatment and four restating. Parameter that evaluated include dry matter intake, consumption of crude protein, protein digestion. Result of the research shown that the average of dry matter intake to T1, T2 and T3 were 958,99; 981,51 and 1242,73 g/goat/day?é?á (P<0,05).?é?á The?é?á average?é?á of?é?á consumption?é?á of?é?á crude protein?é?á to?é?á T1,?é?á T2?é?á and?é?á T3?é?á were?é?á 114,69;?é?á 144,44?é?á and?é?á 233,11 g/goat/day(P<0,05). The average of protein digestion to T1, T2 and?é?á T3?é?á were?é?á 64,22?é?á (55,18%);?é?á 92,83?é?á (64,21%)?é?á and?é?á 156,21 (66,97%)?é?á g/goat/day?é?á (P<0,05).?é?á The?é?á conclution?é?á of?é?á the?é?á research was?é?á levels?é?á of?é?á dietary?é?á protein?é?á as?é?á 18,43%?é?á may?é?á increase?é?á the optimal protein digestion in Peranakan Etawa goat.Keywords : protein, Peranakan Etawa goat